Public policies for liquid biofuels in the Brazilian road transport sector - Zavarise, Julio Pansiere; Vianna, Vinícius Wittig; Pinotti, Laura Marina; Chaves, Gisele de Lorena Diniz; Celeste, Wanderley Cardoso (Brazilian Journal of Production Engineering, 2021)
Brazil has implemented several initiatives aimed at diversifying its energy transport matrix and expanding the use of renewable energies. This article aimed to discuss the current public policies for the adoption of liquid biofuels as fuel, focusing on the Brazilian road sector. For this, a review of the specialized literature was performed. In this context, the main policy discussed in this article was the National Biofuels Policy (RenovaBio), which proposes to reduce the emission of greenhouse gases using biofuels as fuels in road sector. About Renovabio, it is believed that this policy has the potential to significantly increase the supply of biofuels in the Brazilian road transport sector and foster the economic development of the country, although there are political obstacles to be overcome to ensure the full success of its implementation.
Keywords: Biodiesel; Ethanol; Renovabio; Emissions; Rene; Renewable energy